Operator Integral Fraksional yang diperumum pada Ruang Morrey yang diperumum - Putri, Safira Nur Aulia; Rahman, Hairur; Nasichuddin, Achmad (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2024)
The fractional integral operator or Riesz operator is a finite operator of the Lebesgue space. This fractional integral operator maps any real-valued function into the integral form of the fractional integral function. Morrey space is a collection of general form member functions of Lebesgue space. In this study, we will discuss the generalized fractional integral operator on a generalized Morrey space. The proof will be done using partitioned. It can be concluded that the generalized fractional integral operator on Morrey space generalized to Theorem A and Theorems B .